2011
DOI: 10.1007/s00464-011-2048-8
|View full text |Cite
|
Sign up to set email alerts
|

Fetoscopic management of gastroschisis in a lamb model

Abstract: Although technically demanding, we were able to produce and reassess six cases of gastroschisis by fetoscopy. As primary repositioning appears unfavorable, fetoscopic prosthetic bag placement may become an alternative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 13 publications
(16 reference statements)
0
14
0
Order By: Relevance
“…By reviewing the operative video, we found that during the creation of the gastroschisis the procedure was aborted without complete incision of the rectus abdominis muscle due to bleeding. Bleeding was commonly seen during the process of gastroschisis creation; however, it did not lead to fetal demise except in one fetus, which was reported in our earlier series [8]. …”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…By reviewing the operative video, we found that during the creation of the gastroschisis the procedure was aborted without complete incision of the rectus abdominis muscle due to bleeding. Bleeding was commonly seen during the process of gastroschisis creation; however, it did not lead to fetal demise except in one fetus, which was reported in our earlier series [8]. …”
Section: Discussionmentioning
confidence: 48%
“…Nineteen time-dated singleton pregnant German blackhead ewes (Ovis aries orientalis) were used. Of these, 7 animals from our previous publication were included with new data [8]. The access into the uterine cavity was made by sonographically guided percutaneous needle puncture.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though great hopes for reduction of morbidity and mortality are based on fetoscopic repairs, its implementation has been limited due to technical difficulties resulting in premature labor or fetal demise. [1][2][3][4] Consequently, current fetoscopic treatment options are restricted to a well-formulated setting, such as the introduction of a tracheal plug in congenital diaphragmatic hernia, drainage for lower urinary tract obstruction, and coagulation of placental vessels for twin-totwin transfusion syndrome. 5,6 The implementation of more complex fetoscopic procedures has been limited due to technical difficulties that are partly attributed to the different visualization under water.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 The implementation of more complex fetoscopic procedures has been limited due to technical difficulties that are partly attributed to the different visualization under water. 1,2 Some authors propose to insufflate carbon dioxide into the uterus to overcome these obstacles. 7 However, the risks for preterm labor due to fetal stress after intrauterine carbon dioxide insufflation are high and the transfer of this technique to humans seems unadvisable.…”
Section: Introductionmentioning
confidence: 99%